Organizational Tactics An Approach to Strategic Agility A field study in a sample of mobile operators in Iraq - عبودي, صفاء ادريس; خروفة, رغد محمد (Journal of Economics and Administrative Sciences, 2018)
The current research dealt with the issue of organizational skillfulness as an entry point to reach strategic agility. The study has been tested in Iraq's mobile operators - Asia Cell, Zain Iraq and Cork Telecom. The study was applied to a sample of (93) managers distributed at various levels of management (board members, general managers, commissioners, department managers, people managers, unit managers, office managers). The survey used the questionnaire as a key tool for collecting data and information as well as personal interviews. It has sought to test a number of hypotheses related to correlation and influence relationships between the variables of the study, in order to answer the questions related to the problem of study and reach the goals set. In order to process the data and information, many statistical methods were used: the Runs test (kruskal-waills). The study reached a number of conclusions, including the existence of significant differences in both the dimensions of organizational skill and the removal of strategic fitness. The variables are characterized by complete randomness in the election and complete independence from the rest of the variables of the study as well as the existence of significant moral effects towards the organizational skill in the fitness strategy.